Differences in the response to in-phase and out-of-phase multiaxial high-cycle fatigue loading - Jan Papuga; Martin Nesládek; Josef Jurenka (Fracture and Structural Integrity)
This paper discusses the phase shift effect occurring between two and more load channels of multiaxially loaded specimens. The discussion concludes that there is an extreme shortage of good experimental data that would prove the existence and the trend of the phase shift effect in the high-cycle fatigue region. It is no wonder that there are so many fatigue strength estimation criteria that use quite different computational concepts, because the response to the phase shift effect in the experimental base is often hidden in a conglomeration of other interacting effects. The paper presents results of a sensitivity study that compares the fatigue strength estimation results for various such criteria for the same stress amplitudes, but for different phase shifts between the push-pull and torsion load channels. These results show that, with the exception of criteria, that assume a zero phase shift effect, the phase shift affects the results of each studied fatigue strength estimation criterion in a different way. If well-organized experiments were available, experiments corresponding to the described comparison between in-phase and out-of-phase loading would show the right trends, and the optimum criterion could be selected. A proposal for such an experimental setup is provided in the paper.